Pembangunan Sistem Informasi Rawat Jalan dan Rekam Medis Elektronik berbasis Website (Studi Kasus : RSUD Dr. Iskak Tulungagung) - Shinta Aprilisia; Faizatul Amalia; Fitra Abdurrachman Bachtiar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The implementation of health services in a hospital has a very complex organization and organization. Currently, many hospitals, clinics, health centers, and doctors' practices have used information systems to facilitate data management and improve the quality of service to patients. However Dr. Hospital Iskak Tulungagung still faces difficulties in patient registration and searching for medical records. One patient takes 5-15 minutes to complete the registration process, including monitoring patient medical records or creating medical record documents for patients who are first seeking treatment. Seeing these problems, the authors developed an online registration system and electronic medical records, so as to reduce patient queues at registration and maximum patient care. This system will apply the waterfall model for its development process. This model takes a systematic and sequential approach. The test was carried out using a test unit with the whitebox testing method on 3 functions, namely data input, physical examination, changing profiles, adding to the drug list. Of the three test units that have been carried out, it can be declared that they have passed the unit test. The validation results in a valid value in each test case against the 84 tested cases based on 46 functionality, therefore the system is declared to have passed the validation test. In the compatibility test using SortSite resulted in a web that is able to run well on 9 out of 11 browser versions. On the usefulness, the total answers to each of the 10 questions were tested to 20 respondents. The results of the reusability test of this system obtained an average score of 80.4 which is included in the above average classification.